Combinatory effect of osmotic and high pressure processing on shelf life extension of animal origin products – Application to chilled chicken breast fillets. (March 2018) - Andreou, V.; Tsironi, T.; Dermesonlouoglou, E.; Katsaros, G.; Taoukis, P.
Highlights: HP was used as cold pasteurization of OD treated chicken fillets. OD pre-treatment improved texture and color of HP treated chicken fillets. Shelf life was determined based on microbial growth and sensory quality criteria. Combined application of OD and HP extended chilled chicken breast fillet shelf life. Abstract: The objective was to produce chilled chicken breast fillets with extended shelf life using osmotic (OD) and high pressure (HP) processing. Samples were processed in osmotic solution (60% maltodextrin:5% NaCl; 15 °C–45 min), subsequently cold-pasteurized in-pack (600MPa–25 °C–5 min) and stored at 0–15 °C. Quality parameters considered were: microbiological (TVC, Pseudomonas spp., LAB, Brochothrix thermosphacta ), physicochemical (texture, color) and sensory attributes. Both OD and OD-HP combined process led to improved texture and color characteristics. Application of HP alone reduced microbial load and ensured stability during storage, but negatively affected texture (20% increase of hardness) and color of breast fillets (increase of luminosity-color comparable to lightly cooked product). The combined application of OD and HP led to significant extension of shelf life and quality improvement of chicken breast fillets. Based on microbial growth and sensory acceptability the shelf life at 5 °C was estimated as 6, 9, 16, 25 d for untreated, OD, HP and OD-HP samples, respectively.